2011
DOI: 10.1051/0004-6361/201015127
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and physical parameters of eclipsing binaries from the All-Sky Automated Survey catalogue

Abstract: Aims. We present the results of our spectroscopic and photometric analysis of two newly discovered low-mass detached eclipsing binaries found in the All-Sky Automated Survey (ASAS) catalogue: ASAS J093814-0104.4 and ASAS J212954-5620.1. Methods. Using the Grating Instrument for Radiation Analysis with a Fibre-Fed Echelle (GIRAFFE) on the 1.9-m Radcliffe telescope at the South African Astronomical Observatory (SAAO) and the University College London Echelle Spectrograph (UCLES) on the 3.9-m Anglo-Australian Tel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The vast majority of masses for stars and BDs in young clusters can only be determined by comparison with theoretical evolutionary tracks in H-R diagrams, using either luminosity or T eff or both (e.g., Kenyon & Hartmann 1995;Hillenbrand 1997;Luhman et al 1998;Moraux et al 2007;Scholz et al 2012a). While direct mass measurements are available for calibration of these models at higher masses (M 0.3 M ; e.g., Hillenbrand & White 2004), at the lowest stellar masses and into the substellar regime these models are essentially untested.…”
Section: Impact On Estimates Of Object Massesmentioning
confidence: 99%
“…The vast majority of masses for stars and BDs in young clusters can only be determined by comparison with theoretical evolutionary tracks in H-R diagrams, using either luminosity or T eff or both (e.g., Kenyon & Hartmann 1995;Hillenbrand 1997;Luhman et al 1998;Moraux et al 2007;Scholz et al 2012a). While direct mass measurements are available for calibration of these models at higher masses (M 0.3 M ; e.g., Hillenbrand & White 2004), at the lowest stellar masses and into the substellar regime these models are essentially untested.…”
Section: Impact On Estimates Of Object Massesmentioning
confidence: 99%
“…The eclipsing system ASAS J011328–3821.1 (2MASS J01132817–3821024, 1RXS J011328.8–382059, hereafter ASAS‐01) has the shortest orbital period of all the objects in our sample of low‐mass detached eclipsing binaries (LMDEBs; see: Hełminiak & Konacki ; Hełminiak et al ) found in the All‐Sky Automated Survey (ASAS) Catalogue of Variable Stars (ACVS; Pojmański ), and it is one of the shortest among the LMDEBs known to date (i.e. P ASAS = 0.44559 d).…”
Section: The Asas J011328–38211 Systemmentioning
confidence: 99%
“…To directly derive the masses of the components of ASAS‐01, we obtained a series of high‐resolution spectra in order to measure their radial velocities (RVs). Most of the spectroscopic observations come from the 1.9‐m Radcliffe telescope and its Grating Instrument for Radiation Analysis with a Fibre‐Fed Echelle (GIRAFFE) spectrograph at the South African Astronomical Observatory (SAAO), with settings the same as described in the previous papers of this series (Hełminiak et al , ). Five spectra of R ∼ 40 000 were obtained during three consecutive nights in 2006 September.…”
Section: Spectroscopy and Radial Velocitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us note that spots can easily induce RV variations at the level of a few hundreds of m s −1 so the RV variability of BY Dra is not surprising (see e.g. Hełminiak & Konacki 2011; Hełminiak et al 2011). We also had to adopt small shifts between each data set as is explained in Konacki et al (2010).…”
Section: Radial Velocitiesmentioning
confidence: 99%